Potential of herbaceous plant species for copper (Cu) accumulation - Asare, Michael O; Pellegrini, Elisa; Száková, Jiřina; Najmanová, Jana; Tlustoš, Pavel; de Nobili, Maria; Contin, Marco (Environmental science and pollution research international, 2024)
The removal of copper (Cu) in soils by green technology is less treated with urgency, as it is a plant micronutrient. We examined the efficiency of Cu shoot accumulation by herbaceous plants in Cu-contaminated and non-contaminated soils in Trhové Dusniky and Podles, respectively, in the Czech Republic. The total soil Cu content of 81 mg kg-1 in Trhové Dusniky indicated a slight contamination level compared to 50 mg kg-1, the permissible value by WHO, and < 35 in Podlesí, representing a clean environment. The Cu content was above the permissible value in plants (10 mg kg-1 by WHO) in herbaceous speciesat the control site without trees: Stachys palustris L. (10.8 mg kg-1), Cirsium arvense L. (11.3 mg kg-1), Achillea millefolium L. (12.1 mg kg-1), Anthemis arvense L. (13.2 mg kg-1), and Calamagrostis epigejos L. (13.7 mg kg-1). In addition, Hypericum maculatum Crantz (10.6 mg kg-1), Campanula patula L. (11.3 mg kg-1), C. arvense (15 mg kg-1), and the highest accumulation in shoot of Equisetum arvense L. (37.1 mg kg-1), all under the canopy of trees at the uncontaminated site, were above the WHO value. Leucanthemum Vulgare (Lam.) and Plantago lanceolata L. recorded 11.2 mg kg-1 and 11.5 mg kg-1, respectively, in the soil of the Cu-contaminated site. These herbaceous species can support the phyto-management of Cu-contaminated soils, especially E. arvense. Critical attention is well-required in the medicinal application of herbaceous plants in treating human ailments due to their Cu accumulation potentials above the threshold. Spontaneous surveys and analysis of Cu speciation in herbaceous species can reveal suitable plants to decontaminate soils and provide caution on consumable products, especially bioactive compounds.
Keywords: rostliny; látky znečišťující půdu; stromy; Trace Elements; Copper; Biodegradation, Environmental; biodegradace; Phyto-management; měď; Trees; Plants; Herbaceous plants; půda; Soil Pollutants; Humans; Soil; stopové prvky; Equisetum arvense; lidé; Copper-shoot accumulation